Knowledge of Covid-19 and Psychosocial Experiences During the Covid-19 Lockdown among Secondary School Students in Eleyele, Ibadan, Oyo State, Nigeria (2022)
Background: COVID-19 Is A Highly Contagious Disease That Can Easily Spread from Person to Person and Is a Global Health Threat. The Ongoing COVID-19 Is Inducing Fear and Knowledge of the Disease Will Help to Dissipate Fear. The Lockdown That Was Introduced at the Earlier Onset in Many Countries Including Nigeria Was Sudden and This Had Implication for Physical and Psychological State of Individuals Especially Young People, Who Are Easily Bored. Assessment Of Young People’s Knowledge and Psychosocial Experience During the Lockdown Was the Objective of This Study. This Was Done to Provide Baseline Information About Their Experience During This Unprecedented Event. Methods: A Descriptive Cross-Sectional Survey Was Conducted Among 352 Respondents from Five Schools During the First Reopening of Schools for Those in JSS3 And SSS3 Who Were Due for External Examinations. Simple Random Sampling Was Used for Selection of Schools, While Systematic Sampling Was Used to Select Respondents. Data Were Generated From 28th September to 2nd Of October, 2020. Data Were Analyzed Using Descriptive and Inferential Statistics of Chi-Square Test At 0.05% Level of Significance Results: More Than Half (57.1%) Were Females, 55.7% Were Between 15-19 Years with Mean Age Of 14.7± 1.910, 54.3.0% Were in Third Year of Senior Secondary, 56.8% Were from Oyo State, 84.7% Are from Yoruba Ethnic Group and More Than Half Live with Both Parents. More Than Half (58.8%) Had Good Knowledge Of COVID-19, 56.0% Had Positive Psychological Experiences And 57.7% Had Positive Social Experience. Psychological (P=0.101) And Social Experiences (P=0.192) Were Not Significantly Associated with Level of Knowledge Of COVID-19. Conclusion: More Than Half of the Students Had Good Knowledge Of COVID-19, Positive Psychological and Positive Social Experiences. Regular Health Education About COVID-19 And Its Prevention Is Needed to Sustain the Positive Behavior Among the Students and Curb the Spread Of COVID-19.